Estimating Time-Varying Coefficients With the VC Program - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
The estimation of models with time-varying coefficients is usually performed by Kalman-Bucy filtering. The two-sided filter proposed by Schlicht (1988) is statistically and computationally superior to the one-sided Kalman-Bucy filter. This paper describes the estimation procedure and the program package that implements the two-sided filter.
urn:nbn:de:bvb:19-epub-34-5
Keywords: C22; 330; Kalman filtering; Kalman-Bucy; random walk; time-varying coefficients; adaptive estimation; time-series